2011
DOI: 10.1021/bi2012355
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Orotidine 5′-Monophosphate Decarboxylase-Catalyzed Reaction: Importance of Residues in the Orotate Binding Site

Abstract: The reaction catalyzed by orotidine 5’-monophosphate decarboxylase (OMPDC) is accompanied by exceptional values for the rate enhancement [kcat/knon = 7.1 × 1016] and catalytic proficiency [(kcat/KM)/knon = 4.8 × 1022 M−1]. Although a stabilized vinyl carbanion/carbene intermediate is located on the reaction coordinate, the structural strategies by which the reduction in the activation energy barrier is realized remain incompletely understood. This laboratory recently reported that “substrate destabilization” b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Because development of the O4 anion resonance structure is essential for stabilization of a carbene-like intermediate, the relatively small stabilization effects by the Ser-127 backbone amide suggest that it is unlikely to be a major resonance form for the decarboxylation intermediate. Therefore, in the context of the 10 17 rate enhancement (23-kcal/mol decrease in ΔG ‡ ), the interaction between the backbone amide and O4 provides one of several modest contributions; others include substrate destabilization by enforced proximity of the substrate carboxylate group to Asp-70 in an otherwise hydrophobic pocket (5,8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because development of the O4 anion resonance structure is essential for stabilization of a carbene-like intermediate, the relatively small stabilization effects by the Ser-127 backbone amide suggest that it is unlikely to be a major resonance form for the decarboxylation intermediate. Therefore, in the context of the 10 17 rate enhancement (23-kcal/mol decrease in ΔG ‡ ), the interaction between the backbone amide and O4 provides one of several modest contributions; others include substrate destabilization by enforced proximity of the substrate carboxylate group to Asp-70 in an otherwise hydrophobic pocket (5,8).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, two structural strategies have been proposed for stabilization of the anionic intermediate ( Fig. 1B): (i) an enhanced hydrogen-bonding interaction between the Ser-127 backbone amide and O4 of the pyrimidine moiety of the intermediate through a carbene resonance structure (anionic charge on O4) (8,11,15) and (ii) electrostatic interactions between the anionic charge on carbon-6 with the e-ammonium group of Lys-72 (4,9). Both are challenging to test: (i) substitutions for backbone amide groups are difficult to construct, and (ii) Lys-72 is the essential general acid catalyst.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…10 17 [151]. The catalytic mechanism of ODC has been subject to numerous investigations by both experimental [154][155][156][157][158][159][160][161][162][163][164] and computational [156,[165][166][167][168][169][170][171][172] means. In particular, Rishavy and Cleland employed 13 C and 15 N KIEs to elucidate the mechanism [164], and concluded that the most likely pathway involves a direct decarboxylation with an anionic intermediate [162,173].…”
Section: Heavy-atom Kinetic Isotope Effects As a Mechanistic Tool In mentioning
confidence: 99%